2017
DOI: 10.1016/j.neuron.2017.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Effects of apoE Reduction Using Antisense Oligonucleotides in a Model of β-amyloidosis

Abstract: Summary The apolipoprotein E (APOE) gene is the strongest genetic risk factor for late-onset Alzheimer disease. Previous studies suggest reduction of apoE levels through genetic manipulation can reduce Aβ pathology. However, it is not clear how reduction of apoE levels after birth would affect amyloid deposition. We utilize an antisense oligonucleotide (ASO) to reduce apoE expression in the brains of APP/PS1-21 mice homozygous for the APOE-ε4 or APOE-ε3 allele. ASO treatment starting after birth led to a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
138
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 35 publications
7
138
2
2
Order By: Relevance
“…Recombinant E4 has been reported to increase Aß production by receptor-mediated effects, 63 and in transgenic mouse models, E4 promotes the seeding of amyloid plaques. 4,5,63 Aß can in turn induce tau phosphorylation via GSK3ß activation. 64 In our neuronal cultures, genetic correction of E4 did not increase APP expression, Aß42/Aß40 ratio, or GSK3ß phosphoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant E4 has been reported to increase Aß production by receptor-mediated effects, 63 and in transgenic mouse models, E4 promotes the seeding of amyloid plaques. 4,5,63 Aß can in turn induce tau phosphorylation via GSK3ß activation. 64 In our neuronal cultures, genetic correction of E4 did not increase APP expression, Aß42/Aß40 ratio, or GSK3ß phosphoactivation.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the results presented here are the first observations measuring new protein production of long‐lived protein targets in the CNS after therapeutic intervention. Our approach can be directly applied to multiple RNA‐directed strategies, such as siRNAs 31 and ASOs,32, 33 that target long‐lived proteins in neurodegeneration for clinical trials. Besides its lowered protein production readout, stable isotope labeling could be a powerful tool to examine increased protein production for therapeutic strategies such as gene therapy 34 and splicing ASO treatments 35, 36.…”
Section: Discussionmentioning
confidence: 99%
“…These mice were crossed with APP/PS1 mice, which express familial AD mutations that lead to Aβ deposition, thus acting as a model of Aβ amyloidosis. In these mice, the authors confirmed the known effect of ApoE4 expression, where mice expressing the ApoE4 allele have a more severe Aβ pathology compared with mice expressing ApoE3 (8,9). In order to assess the impact of neuronal LRP1 expression on Aβ pathology in the context of ApoE3 and ApoE4, APP/PS1; ApoE3 and APP/ PS1; ApoE4 mice were crossed to neuronal LRP1 knockout (nLrp1 -/-) mice.…”
Section: Apoe4-mediated Seeding Of Aβ Is Dependent On Neuronal Lrp1mentioning
confidence: 72%
“…In sporadic cases, seeding of Aβ has been hypothesized to be due to a variety of causes, including accumulation of Aβ in early endosomes, slowed or altered soluble Aβ clearance, and somatic gene replication, resulting in overexpression of Aβ (5)(6)(7). Apolipoprotein E (ApoE), specifically the ApoE4 allele, contributes to the seeding process in vivo (8,9). Human ApoE has three major isoforms: ApoE2 (Cys112, Cys158), ApoE3 (Cys112, Arg158), and ApoE4 (Arg112, Arg158).…”
mentioning
confidence: 99%
See 1 more Smart Citation